2017
DOI: 10.3390/met7060221
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Nd:YAG Fiber Laser Welding of Ti-6Al-4V Alloy

Abstract: Abstract:In the present study, Ti6Al4V titanium alloy plates were joined using a robotic fiber laser welding method. The laser welding process was carried out at two different welding speeds. Effects of different heat input conditions on the microstructure and mechanical properties of robotic fiber laser welded joints were investigated. Some grain coarsening was observed in the microstructure of weld metal in samples joined using high heat input, compared to those using low heat input, and volume rates of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…In welding titanium and its alloys, a narrow welding seam and a microstructure made of fine grains should be achieved by lowering the heat input transfer to the weld zone and increasing the cooling rate. On the other hand, very fast cooling conditions lead to weld metal microstructures that are completely martensitic in nature and thus have a lower toughness [24][25][26][27]. Cui Li et al [28] also observed a significant grain coarsening occurred in the HAZ immediately adjacent to the base metal, and the degree of grain coarsening increases as the grains move towards the centre of the fusion zone.…”
Section: Introductionmentioning
confidence: 99%
“…In welding titanium and its alloys, a narrow welding seam and a microstructure made of fine grains should be achieved by lowering the heat input transfer to the weld zone and increasing the cooling rate. On the other hand, very fast cooling conditions lead to weld metal microstructures that are completely martensitic in nature and thus have a lower toughness [24][25][26][27]. Cui Li et al [28] also observed a significant grain coarsening occurred in the HAZ immediately adjacent to the base metal, and the degree of grain coarsening increases as the grains move towards the centre of the fusion zone.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, a number of scientific studies are available in the literature dealing with laser beam welding of titanium alloys [ 6 , 7 ], which are widely used in aerospace thanks to their high strength in combination with low density and good tensile properties; medical and surgical devices are even produced using these alloys, thanks to high biocompatibility [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ti6Al4V titanium alloy is widely used in the aerospace, marine, pressure vessel, and chemical industries, as well as for surgical implant, etc., owing to its unique properties, such as a high strength-to-weight ratio, excellent high-temperature properties and corrosion resistance; furthermore, the usage of Ti6Al4V alloy accounts for over 50% of the total titanium alloy tonnage, globally [1][2][3][4][5]. Many welding methods, such as tungsten inert gas welding (TIG) [6,7], laser welding [8], electron beam welding [9], plasma arc welding [10], line friction welding [11][12][13], and friction stir welding [14,15] have been employed to weld titanium alloy in previous investigations.…”
Section: Introductionmentioning
confidence: 99%